Optimizing Student Activities and Learning Outcomes through Problem Solving Models in Stoichiometry Material - Siti Jumaera; Olotu Temitope Blessing; Nyanjiga Rukondo (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: This study aims to improve student activity and learning outcomes by applying the Problem Solving learning model. Methodology: This research is a Classroom Action Research conducted in two cycles, with each cycle consisting of planning, implementation, observation and reflection. The subjects of the research were 33 students of class XC of State Senior High School 1 Wawonii. Data sources came from teachers and students. Data collection techniques were tests and non-tests (observation, document review). Data analysis used qualitative descriptive analysis techniques.. Main Findings: The results of the study showed that: Problem Solving model learning can improve student activity and learning outcomes, namely 71.00% in cycle I increasing to 85.33% in cycle II. Problem Solving model learning can improve student learning outcomes. The percentage of student learning outcome completion reached 64.63% in cycle I increasing to 81.82% in cycle II. From this study it can be concluded that the application of problem solving models can improve student activity and learning outcomes on the subject of stoichiometry. Novelty/Originality of this study: This study offers novelty by applying the Problem Solving Model to improve student learning activities and learning outcomes in Stoichiometry material, which has been considered difficult by many students.